PEMBERDAYAAN ANAK-ANAK PANTI ASUHAN NANGGALO PADANG DENGAN PELATIHAN KERAJINAN TENUN KARTU - Yasrul Sami; Erwin A; Eliya Pebriyeni; Ernis Ernis; Syafwandi Syafwandi (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2018)
Most of the children in the Al Ihsan Orphanage and the Aisyiah Nanggalo Orphanage in Padang do not yet have adequate skills, so that if they leave the orphanage they are afraid that they cannot be independent. For this reason, they are fostered by providing various types of skills as a means of life, so that they can leave the institution and can even create new jobs. Unfortunately the skills given in this institution are very limited and not varied. Factors that cause the lack of variety in the types of skills provided or carried out at this orphanage are; 1) lack of experts from various types of skills and 2) lack of funds for implementation, even though there is assistance from the government and the community but not enough. The types of skills that are often carried out are sewing sewing, while the type of crafting skill has never been given. Though most orphanage children (57%) have artistic talent. For this reason, the leadership of the institution hopes that there will be training in the manufacture of handicrafts for their caregivers Based on the above problems, it was agreed with the two leaders of the Orphanage partners, that the priority issues to be resolved were related to the lack of children's skills, especially craft skills. The solution offered to overcome this problem is to do craft skills training. The type of craft given is card weaving craft. The results of this activity are that in general (81.25%) the children of the Al Ihsan and Aisyiah orphanages in Nanggalo Padang District have the ability to make hand-woven card crafts in good categories